Telaah Filosofis, Yuridis, dan Sosiologis dalam Konteks Hukum Islam Kontemporer terhadap Syariah dan Qanun - Annisaa, Winona Nur; Aunillah, Fahmi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Islamic law plays a central role as the foundation in shaping the social life of Muslim communities. As time progresses and social dynamics evolve, the understanding of Islamic law has also undergone significant development. The term